Recursive percentage based hybrid pattern (RPHP) training for curve fitting - GUAN, Sheng Uei (Institutional Knowledge at Singapore Management University, 2004)
In this paper, we present the RPHP training algorithm, which finds several good local optimal points (pseudo global optima) automatically using an efficient combination of global and local search algorithms. This overcomes the problem of supervised learning algorithms being trapped in a local optima. Further, to solve a test pattern, we use a modified version of the Kth nearest neighbor (KNN) algorithm as a second level pattern distributor. We tested our approach on three curve fitting problems, whose coefficients were estimated both using genetic algorithms and the RPHP algorithm. The problems were chosen such that they had a small probability of finding a global optimal solution. It was found that the RPHP algorithms performed faster and improved generalization accuracy by as much as 25%.